Contribution of the ?8 integrin chain to the expression of extracellular matrix components - Volkert, Gudrun; Jahn, Angelika; Dinkel, Christina; Fahlbusch, Fabian; Zuern, Christina; Hilgers, Karl Friedrich; Rascher, Wolfgang; Marek, Ines; Hartner, Andrea (Cell Communication and Adhesion, 2014)
In the kidney, the ?8 integrin chain (itga8) is expressed in mesenchymal cells and is upregulated in fibrotic disease. We hypothesized that itga8 mediates a profibrotic phenotype of renal cells by promoting extracellular matrix and cytokine expression. Genetic itga8 deficiency caused complex changes in matrix expression patterns in mesangial and smooth-muscle cells, with the only concordant effect in both cell types being a reduction of collagen III expression. Silencing of itga8 with siRNA led to a decline of matrix turnover with repression of matrix metalloproteinases and reduction of matrix production. In contrast, de novo expression of itga8 in tubular epithelial cells resulted in reduced collagen synthesis. Overexpression of itga8 in fibroblasts did not change the expression of matrix molecules or regulators of matrix turnover. Thus, the influence of itga8 on the expression of matrix components was not uniform and celltype dependent. Itga8 seems unlikely to exert overall profibrotic effects in renal cells.
EVALuna2:3701